Strategies of Haze Risk Reduction Using the Tripartite Game Model - Chaoyu Zheng; Benhong Peng; XinSheng; Ehsan Elahi; Anxia Wan (Complexity)
Although haze risk management is mainly under government control, willingness of stakeholders is compulsory to determine. Therefore, this study constructs a tripartite game model of government, public, and enterprises and determines the haze risk evolution model considering the initial willingness of stakeholders. Moreover, numerical simulation analysis was also conducted. The results revealed that stakeholders were affected by the change due to initial willingness to participate in and reach the equilibrium at different speeds. It is found that if subsidy coefficient of the government is big, it will reach equilibrium faster. The bigger the penalty coefficient is, the better the pollution reduction effect of pollutant discharge enterprises. It is found that, at the final equilibrium stage, the government will eventually choose to withdraw from supervision, but the speed of withdrawing varies with different regulatory intentions. Study results stress that the government should actively participate in supervision to reduce environmental pollution.